Personal email manager [electronic resource] - 345577 Chan, Hwee Farn (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2004